The Interplay Between the Natural Number Bias and Fraction Magnitude Processing in Low-Achieving Students - Reinhold, Frank; Obersteiner, Andreas; Hoch, Stefan; Hofer, Sarah Isabelle; Reiss, Kristina (Frontiers in Education, 2020)
Research has identified two core difficulties many students have with fractions: First, they often struggle with processing fraction magnitudes, and second, they rely on natural number concepts in fraction problems (“Natural Number Bias”, NNB). Yet, the relation between these two difficulties is not well understood. Moreover, while most studies of the NNB relied on analyses of the whole samples, there is empirical evidence that the occurrence of the NNB differs between student subgroups. In the present study, we investigate individual students’ profiles of the occurrence of the natural number bias and their ability to process fraction magnitude, using a dynamic assessment that utilizes continuous diagrams on touchscreen devices. We analyze data of 234 low-achieving 6th-grade students from Germany who completed a symbolic fraction comparison task, and a fraction magnitude estimation task with continuous circle and tape diagrams. A cluster analysis on the comparison task revealed three distinct clusters: a Typical Bias cluster (better performance on symbolic fraction comparison items congruent to natural number-based reasoning), a Reverse Bias cluster (better performance on items incongruent to natural number-based reasoning), and a No Bias cluster (similar performance on congruent and incongruent items). Only students in the No Bias cluster but not students in the other clusters demonstrated a distance effect in symbolic fraction comparison, suggesting fraction magnitude processing. Linear mixed models on the percent absolute error in the magnitude estimation task revealed significantly lower percent absolute error for students in the No Bias cluster compared to students in the other two clusters. Moreover, students in the No Bias cluster were significantly slower to solve both fraction comparison and fraction magnitude estimation tasks than students in the other clusters. These results suggest that the occurrence of the natural number bias and the ability to process fraction magnitude are closely related. The continuous representations used in our digital assessment tools appeared to be suitable for assessing both the natural number bias and fraction magnitude processing.